2003
DOI: 10.1002/chem.200390117
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study of Regioselectivity in a Cyclodextrin‐Mediated Diels–Alder Reaction: Revelation of Site Selectivity and the Importance of Shallow Binding and Multiple Binding Modes

Abstract: The use of a cyclodextrin.Diels-Alder transition structure complex (CD.TS) as a model in molecular dynamics simulations has enabled us to gain insight into the controlling factors in the cyclodextrin-mediated Diels-Alder reaction of methyl-p-benzoquinone with isoprene. MD simulations were carried out with multiple binding configurations of the CD.TS (TS=meta-TS, para-TS) complexes at the top and bottom rims of beta-CD. We discovered that i) only shallow binding with the CD is necessary for the regioselectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…The sampled structures were then minimized with use of the PR conjugated gradient method to obtain the lowest energy structure in each simulation. A previous study on β-cyclodextrin complexes has shown this method of locating low-energy structures to be superior to using the Monte Carlo multiple minimum (MCMM) search in MacroModel . During the MD simulations, the guest changes orientation and position in the host, but no decomplexation was observed.…”
Section: Methodsmentioning
confidence: 99%
“…The sampled structures were then minimized with use of the PR conjugated gradient method to obtain the lowest energy structure in each simulation. A previous study on β-cyclodextrin complexes has shown this method of locating low-energy structures to be superior to using the Monte Carlo multiple minimum (MCMM) search in MacroModel . During the MD simulations, the guest changes orientation and position in the host, but no decomplexation was observed.…”
Section: Methodsmentioning
confidence: 99%
“…According to the results, the Root Mean Square Deviation (RMSD) was 0.6Å. It was between the complex's crystal structure and the docked pose [22]. It indicated that CDOCKER module was very believable in this study.…”
Section: Ligand's Analysis Binding and Pharmacophorementioning
confidence: 73%